PENDEKATAN DINAMIS PRINSIP OTONOMI DAERAH TERHADAP KEBIJAKAN PAJAK DAERAH - Putri Utami, Prihatini; Laksmi Danyathi, Ayu Putu (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 03, Mei 2014, 2014)
Seriousness to encourage local governments to tap the Local Revenue has been shown with the revision of the Act No 34 of 2000 on Regional Taxes and Retribution, into the Act No. 28 Year 2009 on Regional Taxes and Retribution. But the problem that occured is how does the dynamic approach between the principle of autonomy on local tax policy in the presence of changes in laws and regulations and whether its accordance to the principle of autonomy in an effort to realize local autonomy. This research using normative legal research method. Local Government has full authority to manage fiscal policy and local income one of the sources of revenue namely Local Taxes, the other side the existence of regional autonomy principle trought the Local Taxes Policy has seen from the Act Amendments of the Local Taxes and Retribution. Amendments the Act No. 28 of 2009 on Regional Taxes and Retribution is accordance with the principle of autonomy in the efforts to achieve the local autonomy.
Keywords: Dynamic approach, Regional Autonomy, Regional Tax